2022
DOI: 10.1186/s12939-022-01642-3
|View full text |Cite|
|
Sign up to set email alerts
|

Does social capital buffer or exacerbate mental health inequality? Evidence from the China Family Panel Study (CFPS)

Abstract: Background Health inequality, including physical and mental health inequality, is an important issue. What role social capital plays in mental health inequality is still ambiguous, especially in developing countries. The aim of this study is to explore the relationship between social capital and mental health inequality in China. Method Both family-level and community-/village-level social capitals are included in our analysis. Data is mainly extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Total scale scores are from 0 to 24, with higher scores representing a higher frequency of depressive symptoms. The reliability and validity have been documented in previous studies (31,32).…”
Section: Depressive Symptoms Inmentioning
confidence: 69%
“…Total scale scores are from 0 to 24, with higher scores representing a higher frequency of depressive symptoms. The reliability and validity have been documented in previous studies (31,32).…”
Section: Depressive Symptoms Inmentioning
confidence: 69%
“…Third, the 2018 CHARLS sample set was replaced by the 2018 China Family Panel Studies (CFPS) and the 2018 Chinese General Social Survey (CGSS). CFPS is a nationwide, comprehensive social tracking survey designed to reflect social, economic, demographic, educational, and health changes in China by tracking and collecting data at the individual, household, and community levels ( 51 ). CGSS is the earliest national, comprehensive, and continuous academic survey project in China that systematically and comprehensively collects data at multiple levels of society, communities, households, and individuals ( 52 ).…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…There is strong evidence that, on average, the impact of social capital on mental well-being is positive. Studies have shown a higher level of social capital is related to fewer depressive symptoms ( Howley, Neill & Atkinson, 2015 ; Simons et al, 2020 ; Cao et al, 2022 ). This may be due to communities with high levels of social capital are more likely to discourage behaviors such as drinking, smoking, and crime, and even promote mentally healthier behaviors, such as regular exercise ( Giordano & Lindstrom, 2010 ; Tennison et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%